Sleep deficiencies and suicidal ideation across the psychosis continuum - Wastler, Heather M.; Blouin, Alexandra M.; Kilicoglu, Melissa F. V.; Bozzay, Melanie (Frontiers in Psychiatry, 2025)
ObjectiveSleep deficiency, a broad term that encompasses sleep disorder symptoms and other aspects of disturbed sleep, is an established risk factor for suicide. Although several studies have examined the relationship between sleep, suicidal ideation, and suicide attempts among individuals with psychotic disorders, few studies have focused on the early stages of illness. The current study addressed this gap in the literature by examining the relationship between sleep deficiencies, recent suicidal ideation, and lifetime suicidal behavior across the psychosis continuum.MethodA retrospective chart review was used to obtain relevant data for individuals at clinical high-risk for psychosis (CHR-P), individuals with first-episode psychosis (FEP), and individuals with longstanding illness.ResultsResults indicate that sleep deficiencies are prevalent across all stages of illness, though individuals at CHR-P have significantly higher rates of sleep deficiency than individuals with FEP and longstanding psychosis. Additionally, there was a strong relationship between sleep deficiencies and suicidal ideation across the entire sample.ConclusionsFurther research is needed to clarify the specific nature of these sleep deficiencies and to elucidate the mechanisms by which sleep deficiencies might increase risk for suicide in this population.